2017
DOI: 10.1186/s13075-017-1282-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased galectin-3 may serve as a serologic signature of pre-rheumatoid arthritis while markers of synovitis and cartilage do not differ between early undifferentiated arthritis subsets

Abstract: BackgroundUndifferentiated arthritis (UA) is a label applied to patients with joint complaints which cannot be classified according to current criteria, which implies a need for precision diagnostic technologies. We studied serum galectin-3, a proinflammatory mediator, and seromarkers of structural joint elements in patients with early, UA and their associations with disease profile and biochemical and imaging findings.MethodsOne hundred and eleven UA patients were followed-up for at least 12 months and reclas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 34 publications
2
15
0
3
Order By: Relevance
“…In their small series of long‐standing RA patients, these authors found that galectin‐3 was increased in synovial fluid and serum compared with osteoarthritis patients and healthy controls. In addition, our group has recently reported that galectin‐3 is higher in pre‐RA than in early, undifferentiated arthritis of non‐RA origin . Additional experimental research has provided further evidence for a role of galectin‐3 in the RA disease pathway.…”
Section: Introductionmentioning
confidence: 81%
“…In their small series of long‐standing RA patients, these authors found that galectin‐3 was increased in synovial fluid and serum compared with osteoarthritis patients and healthy controls. In addition, our group has recently reported that galectin‐3 is higher in pre‐RA than in early, undifferentiated arthritis of non‐RA origin . Additional experimental research has provided further evidence for a role of galectin‐3 in the RA disease pathway.…”
Section: Introductionmentioning
confidence: 81%
“…Gal-3 was reported to contribute to the activation of RA synovial fibroblasts [ 377 ] and to promote the production of pro-inflammatory cytokines, such as interleukin-6 and tumor necrosis factor-α, in synovial fibroblasts [ 381 , 382 ]. For all these reasons the Gal-3 serum level was proposed as a predictive marker of future RA [ 383 ]. According to this study, the increase of serum levels of Gal-3 may help in discriminating between patients with undifferentiated arthritis who subsequently developed RA and those with undifferentiated arthritis who do not develop RA and in this sense it works better than other serological markers of cartilage regeneration (such as the type IIA collagen N-terminal propeptide, PIIANP) or synovial swellings (such as the hyaluronan, HYA).…”
Section: Rmentioning
confidence: 99%
“…Gal-3 has been reported to be expressed and secreted by inflamed synovium in patients of rheumatoid arthritis and osteoarthritis. Issa and colleagues reported that Gal-3 serum levels was persistently increased in early rheumatoid arthritis, and a positive correlation was observed between Gal-3 serum levels and some associated pathophysiology, such as autoimmunity, smoking, and joint destruction [72,120]. In experimental animal models for osteoarthritis, Gal-3 has been demonstrated to induce joint swelling and osteoarthritis-like lesions after intra-articular injection [119].…”
Section: Rheumatoid Arthritis and Osteoarthritismentioning
confidence: 99%